THE EFFECTIVENESS OF VIDEO DENTAL HEALTH EDUCATION SPECIAL NEEDS CHILDREN ON THE ORAL HYGIENE STATUS - Renie Kumala Dewi; Anugrah Qotrunnada Hakim; Beta Widya Oktiani; Nabila Nabila (Dentino : Jurnal Kedokteran Gigi, 2022)
Background. The clinical oral cavity characteristics of children with intellectual disabilities include a high prevalence of periodontal disease and dental caries. South Kalimantan is a wetland or marsh that contains acidic water with a pH of 3.5-4.5. The acidic condition causes tooth demineralization, which can lead to caries. Oral health education through special needs children dental health education (DHE) interactive video is needed. Objective. Analysing the effectiveness of dental health education (DHE) video media for special needs children living in wetlands during the Covid-19 pandemic on the oral hygiene status of children with intellectual disabilities. Methods. The study used a quasi-experimental design with a pretest, posttest without control design and using a simple random sampling technique. The samples were 52 children with intellectual disabilities who were subjected to the OHI-S examination before watching a DHE video for children with intellectual disabilities made by the author as a pretest. Afterward, the children were instructed to watch a 5-minute video made by the author using the Makaton method. Posttest involved OHIS reexamination after watching the video for 20 consecutive days. Data were analysed using the Wilcoxon statistical test. Results. There were 29 children with fair OHI-S (55.8%), 15 with poor OHI-S (28.8%), and 8 with good OHI-S (15.4%). The result of the Wilcoxon test indicated a value of 0.000 (p < 0.05). Conclusion. OHI-S score before the DHE video treatment was fair and improved to good after the DHE video. DHE video can increase the OHI-S in children with intellectual disabilities. Keywords: Covid-19, Dental Health Education Video, Oral Hygiene Index Status, Special needs children video.